Effect of Microgravity on the Gut Microbiota Bacterial Composition in a Hindlimb Unloading Model - Ruqaiyyah Siddiqui; Rizwan Qaisar; Naveed Ahmed Khan; Ahmad M. Alharbi; Hasan Alfahemi; Adel Elmoselhi (Life, 2022)
We utilised a ground-based microgravity hindlimb unloading (HU) mouse model to elucidate the gut microbiota bacterial changes in mice under a simulated microgravity environment. Four-month-old, male C57/Bl6 mice were randomly divided into ground-based controls and the HU groups and kept under controlled environmental conditions. For the microgravity environment, the mice were suspended in special cages individually for 20 days. At the end of the suspension, the mice were sacrificed; gut dissections were performed, followed by a metagenomic analysis of bacterial species, which was carried out by extracting DNA and 16S rRNA analysis. The results revealed that the gut bacterial communities of mice under gravity and microgravity were different. Notably, our findings revealed differences in the bacterial community structure. Around 449 bacterial OTUs were specific to mice kept under normal gravity versus 443 bacterial OTUs under microgravity conditions. In contrast, 694 bacterial OTUs were common to both groups. When the relative abundance of taxa was analyzed, Bacteroidetes dominated the gut (64.7%) of normal mice. Conversely, mice in the microgravity environment were dominated by Firmicutes (42.7%), and the relative abundance of Bacteroidetes differed significantly between the two groups (p < 0.05). The distribution of Muribaculaceae between normal mice versus microgravity mice was significantly different, at 62% and 36.4%, respectively (p < 0.05). Furthermore, a significant decrease in 11 bacteria was observed in mice under simulated microgravity, including Akkermansia muciniphila, Eubacterium coprostanoligenes, Bacteroides acidifaciens, Clostridium leptum, Methylorubrum extorquens, Comamonas testosterone, Desulfovibrio fairfieldensis, Bacteroides coprocola, Aerococcus urinaeequi, Helicobacter hepaticus, and Burkholderiales. Further studies are needed to elucidate gut bacterial metabolites of these identified bacterial species in microgravity conditions and normal environment. Notably, the influence of these metabolites on obesity, neuroprotection, musculoskeletal and cardiovascular dysfunction, longevity, inflammation, health, and disease in astronauts ought to be investigated and will be important in developing procedures against adverse effects in astronauts following space travel.